(untitled) (Argos, 2026)
In the Augustana Collection, where animal protagonists prevail, a number of fables also introduce Olympian gods into the narrative framework. This study focuses on fables involving Zeus and Aphrodite in order to investigate both the modes of divine representation and the ways in which divine agency interacts with the construction of the ‘type’ of the ‘natural wicked’ (πονηρός). In these accounts, the gods modify the φύσις of inferior beings —whether through corporeal metamorphoses, alterations of social rank, or transmutations of species. Such interventions, which generate anger and punishment, not only underscore divine agency as arbitrary and superior, but also problematize, within the rhetorical device of the Aesopic fable, the construction of the ‘πονηρός type’ and its relationship to the divine. Accordingly, the fable is approached as a narrative locus in which divinity is not idealized but permeated by the Collection’s tensions that moves its representation and its interplay with other beings.